2018
DOI: 10.3389/frobt.2018.00009
|View full text |Cite
|
Sign up to set email alerts
|

When It’s Good to Feel Bad: An Evolutionary Model of Guilt and Apology

Abstract: We use techniques from evolutionary game theory to analyze the conditions under which guilt can provide individual fitness benefits, and so evolve. In particular, we focus on the benefits of guilty apology. We consider models where actors err in an iterated prisoner's dilemma and have the option to apologize. Guilt either improves the trustworthiness of apology or imposes a cost on actors who apologize. We analyze the stability and likelihood of evolution of such a "guilt-prone" strategy against cooperators, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Recent research showed the importance of guilty apology in strong friendship [13]. Moreover, opportunities to make amends are more plentiful among friends than among strangers, which lead to the idea that in order to maintain a strong, honest relationship, punishment might sometimes be necessary [10,11,13]. Our finding supports the idea that guilt has a much stronger function and impact within existing friendships, leading to harsher punishments.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Recent research showed the importance of guilty apology in strong friendship [13]. Moreover, opportunities to make amends are more plentiful among friends than among strangers, which lead to the idea that in order to maintain a strong, honest relationship, punishment might sometimes be necessary [10,11,13]. Our finding supports the idea that guilt has a much stronger function and impact within existing friendships, leading to harsher punishments.…”
Section: Discussionsupporting
confidence: 82%
“…Alternatively, it could be that participants evaluate the contribution of their partner differently in light of the guilty look. The guilty look might reinforce the information given to the participant that their partner has performed poorly and act as an acknowledgement of the wrongdoer's bad behaviour [ 13 ]. After receiving the feedback from the game, participants did not interact directly anymore.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations